Mosaic complete tetrasomy 21 in a fetus with complete atrioventricular septal defect and minor morphological variations. Issue 11 (7th September 2019) - Gatinois, Vincent; Bigi, Nicole; Mousty, Eve; Chiesa, Jean; Musizzano, Yuri; Schneider, Anouck; Lefort, Geneviève; Pinson, Lucile; Gaillard, Jean‐Baptiste; Ragon, Clémence; Perez, Marie‐Josée; Tournaire, Magali; et al.
Abstract : Tetrasomy 21 is a very rare aneuploidy which could clinically resemble a Down syndrome. It was most often described in its partial form than complete. We report the prenatal, pathological and genetic characteristics of a fetus with mosaic complete tetrasomy 21. Abstract: Background: Tetrasomy 21 is a very rare aneuploidy which could clinically resemble a Down syndrome. It was most often described in its partial form than complete. We report the prenatal, pathological and genetic characteristics of a fetus with mosaic complete tetrasomy 21. This is the second well‐documented description of a complete tetrasomy 21 in the literature. Methods: Prenatal and fetal pathological examinations, cytogenetic and molecular analyses were performed to characterize fetal features with tetrasomy 21. Results: Prenatal ultrasound examination revealed an isolated complete atrioventricular septal defect with normal karyotype on amniotic fluid. After termination of pregnancy, clinical examination of the fetus evoked trisomy 21 or Down syndrome. Chromosomal microarray analysis and FISH on lung tissue showed a mosaicism with four copies of chromosome 21 (tetrasomy 21). Conclusion: Our observation and the review of the literature reported the possibility of very weak mosaicism and disease‐causing confined tissue‐specific mosaicism in fetus or alive patients with chromosome 21 aneuploidy, mainly Down syndrome. In case of clinical diagnosis suggestive of Down syndrome, attention must be paid to the risk of false‐negative test due to chromosomal mosaicism (very weak percentage, different tissue distribution). To overcome this risk, it is necessary to privilege the diagnostic techniques without culture step and to increase the number of cells and tissues analyzed, if possible. This study highlights the limits of microarray as the unique diagnostic approach in case of weak mosaic and French cytogenetics guidelines recommend to check anomalies seen in microarray by another technique on the same tissue.